THE INFLUENCE OF INTUBATION ON SWALLOWING IN NEUROSURGICAL PATIENTS - Sales Assunção, Gabryela; Andrade dos Santos de Queiroz, Moisés; de Albuquerque Cabral Silva, Jorgeane; Rolim Teixeira Henderson, Mozart Ney; Laurindo Porto , Andrea Cintia; Praça Brasil, Christina Cesar (Cadernos ESP, 2023)
To analyze the influence of short-term orotracheal intubation (OTI) on swallowing in postoperative neurosurgical patients. Longitudinal, observational, descriptive and prospective study carried out in the intensive care unit. The sample consisted of 90 patients, who were submitted to the Speech Therapy Protocol of Introduction and Transition of Oral Feeding for patients at risk for Oropharyngeal Dysphagia and Videoendoscopy of Swallowing Protocol (VED). Patients underwent assessments between 6-12 hours after extubation. In the clinical speech-language evaluation of swallowing, 80% of the patients had normal swallowing. This was also evidenced during the VED in 72.2% of the cases, with no statistical difference between the two methods of evaluating swallowing at the bedside. Patients undergoing short-term OTI present the possibility of starting an oral diet after a period of six hours, but with possible restrictions regarding the food consistency consumed.